Strategi Orang Tua dalam Membentuk Perilaku Sopan Santun pada Anak Usia 9-10 Tahun di Desa Lebo RT 12 RW 03 Sidoarjo - Febrianingrum, Kartika; Nadlif, Ainun; Astutik, Anita Pudji (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The purpose of this research is to show how parents’ strategies in shaping children aged 9-10 years in developing polite behavior. The research method used is a field research method with a descriptive qualitative research approach strategy. The data subjects in this study were two parents or two families who had children aged 9-10 years in Lebo Village RT 12 RW 03 Sidoarjo. The techniques used in this study are observation, interviews and documentation. The result of the data analysis show that the parents’ strategy in shaping polite behavior in children aged 9-10 years in Village RT 12 RW 03 Sidoarjo, parents have implemented the formation of polite behavior through giving advice, giving examples or exemplary reinforcement. A little less accomplished, because parents have not full provided direct guidance. The involvement of parents in the formation of children’s polite attitude with the teaching of religious education as well as moral education.